Strategy for directing public health action in Trinidad and Tobago, 1995-2015 - Patrick, A. Boyd ([s.n.] [S.l.])
Analyses Trinidad and Tobago's current disease profile and presents a methodology for ensuring both health provider and consumer alike know what the country's aims and objectives are, if life expectancy and quality of life is to be improved.